Pengaruh Pemberian Alkohol Peroral Terhadap Nilai Mean Corpuscular Volume, Morfologi Eritrosit Darah Tepi dan Normoblas Sumsum Tulang - Rodhi Hartono; Soewono Soewono; Tri Ratnaningsih (Jaringan Laboratorium Medis, 2019)
A true experimental research with pre-post test control group design was carried out using 36 adult experimental male rats (strain wistar Rattus norvegicus) ,aged 10 weeks with weight of 200-250 grams. Before being given the treatment, the rats blood were taken out around 1,5 cc to measure the MCV value and the erythrocyte morphology. The rats were divided into 6 groups. The first group was the control group and the other five were the treatment group which were treated with different concentration of alcohol continuously for 45 days. After being treated, the rats blood were taken as same as the investigator did previously to examine the MCV value and the erythrocyte morphology, included the removal of right femur to assess morphology and bone marrow normoblast diameter. Results of the study showed that  there was increasing  on  MCV value after the treatment that was proportional to the  alcohol  concentration given (p 0.0000.05), likewise the changing of erythrocyte morphology was in term of acanthocytes  target cells, and stomatocyt . However, these research findings showed that there were no significant different in each group resulting  of the treatment (p 0.817 0.05). Yet,there was an inclination of normoblast diameter. Finally, it can be concluded that consuming oral alcohol continuously increases the MCV value, changing of erythrocyte morphology and bone marrow normoblast.